Do young people stand alone in their demand to live alone? The intergenerational conflict hypothesis put to test in the housing sector - Laura Naegele; Wouter De Tavernier; Moritz Hess; Sebastian Merkel (Intergenerational Justice Review)
The housing sector is currently under pressure: demographic shifts, urbanisation as well as the availability and costs of housing have led to increasing prices. Concerns are being raised that these rising housing costs could lead to intergenerational conflicts. While older generations often live in their privatelyowned dwellings, younger cohorts struggle to become homeowners, moving the field of housing into the spotlight of national debates. We analyse the importance of housing for Europeans using data from Eurobarometer. Results show that the relevance of housing increased between 2008 and 2018. However, generational differences were found: while older and younger people see housing as an important topic at the country level, only the younger generation seems to be affected personally.